2007
DOI: 10.1093/chemse/bjm041
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Long-Term Occupational Exposure to Styrene Vapor on Olfactory Function

Abstract: The primary sensory neurons of the olfactory system are chronically exposed to the ambient environment and may therefore be susceptible to damage from occupational exposure to many volatile chemicals. To investigate whether occupational exposure to styrene was associated with olfactory impairment, we examined olfactory function in 2 groups: workers in a German reinforced-plastics boat-manufacturing facility having a minimum of 2 years of styrene exposure (15-25 ppm as calculated from urinary metabolite concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Transforming the LWAE MA + PGA data into styrene air concentrations, one can assume 25-33 ppm as long-term exposure for the group exposed to high-long levels with job tenure of about 15 years (range up to 26 years). As outlined in section "past and current exposure" higher exposures of 80-100 ppm as average can be assumed for the time period before 1995 (Dalton et al 2007;Triebig et al 1985). Thus, (1) the cases with a hearing loss of more than 25 dB and (2) the group diVerences at 125-1,500 Hz and selectively at 8,000-12,500 Hz as well as (3) the "recovery eVects" at frequencies above 8,000 Hz are probably caused by styrene concentrations of more than 50 ppm as an average.…”
Section: Comparing the Results With Former Studiesmentioning
confidence: 99%
“…Transforming the LWAE MA + PGA data into styrene air concentrations, one can assume 25-33 ppm as long-term exposure for the group exposed to high-long levels with job tenure of about 15 years (range up to 26 years). As outlined in section "past and current exposure" higher exposures of 80-100 ppm as average can be assumed for the time period before 1995 (Dalton et al 2007;Triebig et al 1985). Thus, (1) the cases with a hearing loss of more than 25 dB and (2) the group diVerences at 125-1,500 Hz and selectively at 8,000-12,500 Hz as well as (3) the "recovery eVects" at frequencies above 8,000 Hz are probably caused by styrene concentrations of more than 50 ppm as an average.…”
Section: Comparing the Results With Former Studiesmentioning
confidence: 99%
“…This has already been frequently observed for volatile substances in industry or the laboratory and is correspondingly well documented [126]. Whereas the identification test revealed no differences between exposed and non-exposed individuals in the study published in 2003, the identification test published in 2007 resulted in a significant difference between the workers with high vs. low exposure [125]. Dalton et al state that the proportion of individuals showing poor values in the identification test is substantially higher in both groups (40 and 20%) than in the normal population (10%) [125].…”
Section: Industrial Chemicals With a Potential Impact Upon Olfactionmentioning
confidence: 53%
“…Other epidemiological studies of workers in the glass fibre reinforced plastic industry revealed no relationship between styrene exposure and a general deterioration in olfactory function [124, 125]. In both studies the olfactory threshold for styrene was significantly higher among the exposed workers.…”
Section: Industrial Chemicals With a Potential Impact Upon Olfactionmentioning
confidence: 66%
See 2 more Smart Citations